Toward enhanced quality assurance guidelines for deep hyperthermia devices: a multi-institution study - Mattia De Lazzari; Carolina Carrapiço-Seabra; Dietmar Marder; Gerard C. van Rhoon; Sergio Curto; Hana Dobšíček Trefná (International Journal of Hyperthermia)
Introduction Hyperthermia efficacy depends on the temperatures achieved in the target area. Therefore, hyperthermia systems must deliver both controlled and conformal heating. This study presents a comprehensive multi-institutional quality assurance (QA) evaluation of deep hyperthermia devices.Methods Six European institutions equipped with BSD- Sigma 60 and Sigma Eye deep hyperthermia applicators participated in the study. Up to six measurements per applicator were performed in each institution. The thermal distribution in cylindrical homogeneous phantoms after 10 minutes of heating with a total power delivered of 1000 watts was assessed using the applicator’s integrated mapping thermometry system. Evaluated quality parameters included temperature increase, focus location, and focus symmetry.Results A total of 54 measurements were conducted, with 43 included in the analysis. All applicators, except one, achieved a temperature increase of 6 °C in 10 minutes. Central heating capabilities were demonstrated, with mean deviations from the intended location of −1.4 ± 1.6 cm for Sigma 60 and 1.5 ± 1.4 cm for Sigma Eye. Symmetry evaluations showed differences in radial temperature profiles of 6.2 ± 4.5 % for the Sigma 60 and 5.9 ± 4.4 % for the Sigma Eye. We propose minimum acceptable values for each quality parameter based on these results.Conclusion The measurements were reproducible with acceptable values for the various quality parameters. Potential deviations might be attributed to inaccuracies in the mapping thermometry system rather than the heating system. The presented protocol and practical recommendations should be applied for future QA measurements in deep hyperthermia.